Analysis of the first urban regeneration area in Kocaeli after Gölcük earthquake by using zoning plans - Burcu Aslan; Cankut Dağdal İnce (TeMA: Journal of Land Use, Mobility and Environment, 2019)
Rapidly growing cities following The Industrial Revolution remained insufficient to fulfill today's necessities. Also, natural disasters such as earthquakes, floods or unsound structures have affected the development of cities adversely. Although natural disasters can be unpredictable, the issue of preparing cities for natural disasters, planning cities and regulating laws accordingly are becoming increasingly crucial. Urban regeneration activities are one of these preventions taken in this purpose. It is observed that countries such as Turkey, faced with natural disasters intensively, suffer from serious physical, financial and moral losses. Therefore, urban renewal activities have gained importance in Turkey after The Gölcük Earthquake (7.4Mw) and The Düzce Earthquake (7.2Mw) in 1999. The first urban regeneration project in Kocaeli where was one of the cities experiencing hard collapses of these earthquakes is about to be completed. Research of the principles of urban sustainability and resiliency in urban regeneration practices, which are priority issues due to natural disaster risks, has come into prominence. It is important not only to make urban areas more resistant to disasters but also to design according to social, economic and ecological criteria to make more livable. In this study, social, health, green, transportation and educational areas of the first urban regeneration area in Kocaeli were examined in terms of the basic needs of the city. For this purpose, pre and post-project zoning plans are analyzed and transferred to the GIS. The areal changes in the above-mentioned needs are evaluated for changing population density and their sufficiencies are compared.